Computational repurposing of approved drugs targeting KRAS G12D and EGFR for colorectal cancer therapy - Walaa Ibraheem; Fatima Alsheikh; Abdulrahim A. Alzain; Bhoomendra A. Bhongade; Laila Ejaz; Hamnah Baig; Robert C. Robinson; Mohamed El-Tanani (PLoS ONE, 2026)
Background/objectives Colorectal cancer is characterized by various oncogenic mutations, with the KRAS G12D mutation being the most prevalent. The development of MRTX1133 has revitalized the KRAS direct targeting. However, colorectal cancer demonstrated intrinsic resistance to MRTX1133, primarily due to the feedback activation of the EGFR pathway. Combining KRAS G12D and EGFR inhibition has demonstrated improved treatment efficacy, highlighting the potential of dual-targeting approaches in colorectal cancer therapy. This study employs CADD tools to identify approved drugs capable of dual targeting KRAS G12D and EGFR. Methods A library of 3,591 approved drugs was screened against KRAS G12D using high-throughput virtual screening (HTVs), standard precision (SP) and extra precision (XP) Glide docking modules. The top-ranking compounds were then docked into the EGFR binding pocket using XP mode, and docking scores were calculated. Further refinement of binding affinities was performed using Molecular Mechanics with Generalized Born and Surface Area Solvation (MM-GBSA) and Molecular Dynamics (MD) simulations. Results A total of 25 drugs showed better affinity to KRAS G12D than MRTX1133 (−9.18 kcal/mol). Among them, six drugs: Reproterol, Macimorelin, Nebivolol, Nadolol, Antrafenine, and Carteolol, displayed docking scores between −7.186 and −8.864 kcal/mol against EGFR, compared to the reference ligand Erlotinib (−9.669 kcal/mol). Subsequent MM-GBSA and MD identified Carteolol, an FDA-approved beta blocker, as the most promising candidate, showing stable and reliable binding with KRAS G12D and relatively stable interactions with EGFR. Conclusions This in silico study predicts Carteolol as a potential dual-targeting therapeutic agent, requiring biochemical and cellular validation before clinical relevance can be established.